5m-40=m+60

Simple and best practice solution for 5m-40=m+60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m-40=m+60 equation:


Simplifying
5m + -40 = m + 60

Reorder the terms:
-40 + 5m = m + 60

Reorder the terms:
-40 + 5m = 60 + m

Solving
-40 + 5m = 60 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
-40 + 5m + -1m = 60 + m + -1m

Combine like terms: 5m + -1m = 4m
-40 + 4m = 60 + m + -1m

Combine like terms: m + -1m = 0
-40 + 4m = 60 + 0
-40 + 4m = 60

Add '40' to each side of the equation.
-40 + 40 + 4m = 60 + 40

Combine like terms: -40 + 40 = 0
0 + 4m = 60 + 40
4m = 60 + 40

Combine like terms: 60 + 40 = 100
4m = 100

Divide each side by '4'.
m = 25

Simplifying
m = 25

See similar equations:

| 6(3y-3)-22=3(2y-1)+20 | | X+2y=16y | | 8-3x+1=0 | | 4(z+2)=9z-7 | | 5n-25=90 | | 4y+10=5y+3 | | 3x/5-4=2x | | 16x+32y=42x-16y | | Y=(5/2)-5 | | 2/5x÷1/2=1 | | 60+5x=3.50(x+20) | | y-(-4)=5/4x(x-3) | | 5(6x+5)=3(5x-2) | | 3x-3x=29+17 | | x+5y=4(3y) | | 3x-3x=29-17 | | 6x-13=5x+1+15x | | 5+(-2)*-2*-2= | | 2x-5=7x-6.5-5x | | 9(2-w)=-18 | | -3/8a9/14 | | -21-(-17)= | | -31h=-32h^2 | | x+28=-9x+8 | | -20+5y+35=0 | | 23p^2-21p-2=0 | | (-6)+26+12+(-15)= | | cos(4x)=sin(8x) | | 49x^2-100y^2=0 | | 10+5y+35=0 | | 5+(-2)+(-2)+5= | | -16=4 |

Equations solver categories